Principles for the Design of Business Dictionaries on Mobile Applications - Kwary, Deny A. (HERMES - Journal of Language and Communication in Business, 2013)
The rapid growth of mobile applications for smartphones in the past few years has encouraged dictionary publishers to offer mobile dictionaries. One of the most prominent target markets of mobile dictionary applications is business people, especially those who are non-native speakers of English. These business people often need a dictionary to help them understand the international news they are reading. However, as shown in the review of the current mobile business dictionaries, the dictionary applications have not taken into account the needs of the users and the technological features of smartphones. The current mobile dictionaries still resemble either their electronic versions or even worse their printed versions. This can be due to the lack of research and emphasis on the theoretical aspects of mobile lexicography. Therefore, this paper tries to formulate principles for the design of business dictionaries for mobile applications. The discussion considers the implementation of the modern theory of lexicographical functions in order to create mobile dictionaries which can better satisfy the needs of the users. The principles created are organized into two parts, they are, business news with a built-in dictionary and a dictionary with updated business news.